Cities and Street Art. A Sociological Research on 1UP, Mr. Paradox Paradise, Cranio, Blu and Mr. Woodland - conti, uliano (Italian Sociological Review, 2024)
The paper analyzes the phenomenon of street art and the relationship between street art, graffiti, cities and social actors, such as the audience of the artworks. The paper presents the state of the art related to phenomena of street art, graffiti, and the related subcultures. Then, the article considers original aspects and changes of the relationship between street art and graffiti. This analysis is possible thanks to reference to urban artworks of 1UP collective, Mr. Paradox Paradise, Cranio, Blu, and Mr. Woodland. These artists mark a turning point in the relationship between street art, graffiti, and social actors, and their works are considered as examples for the proposed arguments. In this sense, the global relevance of urban contexts such as Berlin, where some of these artists began their activities, emerges. The changing relationship between street art and graffiti is analyzed in the German capital from the perspective of visual sociology through photographic field research. Photographic research makes the artworks observable and analyzable ex-post. Street art emerges not as a homogeneous phenomenon, but shows different forms of expression, some closely related to traditional graffiti, others profoundly different. Emerging characters are analyzed through the concepts of audience, shock, collective innervation and aura, which refer to the sociological tradition of Walter Benjamin and Siegfried Kracauer, viewed as conceptual lenses for the study of contemporary street art.